A Density Functional Theory Study of the Hydrolysis Mechanism of Sulfachloropyridazine (Communications in Computational Chemistry, 2017)
Sulfonamide antibiotics are an important class of organic pollutant in theaquatic environments. To understand the hydrolysis behavior of sulfonamides, thehydrolysis mechanisms of a typical sulfonamide sulfachloropyridazine (SCP) wereinvestigated using the density functional theory (DFT) at the B3LYP/6-31+G (d, p) level.SCP hydrolysis resembles nucleophilic substitution by water molecule attackingsulfonyl group (pathway 1) and heterocyclic aromatic ring (pathway 2) respectively.Due to the electrophilic center sulfur atom in pathway 1 carrying much larger positivecharge than the carbon atom in the pathway 2, the sulfonyl group can be easilyattacked by water molecule, and thus the pathway 1 can be dominant. By comparingthe hydrolysis energy barrier of different forms of SCP, it was found that the SCPhydrolysis in neutral and once-protonated state are much more energetically favorableto proceed than the double protonated form. In addition, the hydrolysis path is notfound for the dissociated anionic SCP. As the pH values in solution decreases, thecorresponding neutral and once-protonated SCP increases, then the hydrolysis ratebecomes faster, which is consistent with the experimental observations that thehydrolytic degradation rate at pH=4 is much faster than those of pH=7 and 9.
Keywords: Hydrolysis Mechanism; Sulfonamides; Sulfachloropyridazine; the Density Functional Theory (DFT) .